Malignant sacro-coccygeal teratoma with growing teratoma syndrome - Tamador Al-Shamaileh; Fatena Ajlouni; Rasha Deebajah; Iyad Sultan; Mohammad M. Saleem; Khalil Ghandour (Journal of Pediatric Surgery Case Reports, 2019)
A 13-month-old female with sacro-coccygeal tumor type II by Altman, was proven by biopsy to be a malignant germ cell tumor. Serum tumor markers were normal. During neo-adjuvant chemotherapy visible tumor progression was confirmed radiologically and progressed despite changing chemotherapy. The external growing mass forced its way out of the skin. More importantly, CT showed resolution of the pelvic component. Complete tumor resection with coccygectomy was performed. Histopathology showed mature teratoma, immature cells in the coccyx and no malignant germ cells. Three months after ending her therapy she remains in remission. We report the first case of growing teratoma syndrome (GTS) in the coccygeal region. Keywords: Sacro-coccygeal teratoma, Growing teratoma syndrome